CFD Analysis of Nozzle Exit Position Effect in Ejector Gas Removal System in Geothermal Power Plant - Nugroho, Setyo; Citrahardhani, Ciptananda (EMITTER International Journal of Engineering Technology, 2015)
The single stage ejector is used to extract the Non CondensableGas (NCG) in the condenser using the working principle of the Venturi tube. Three dimensional computational simulation of the ejector according to the operating conditions was conducted to determine the flow in the ejector. Motive steam entering through the convergent â divergent nozzle with increasing flow velocity so that the low pressure exist around the nozzle. Comparison is done also in a two dimensional simulation to know the differences occurring phenomena and flow inside ejector. Different simulation results obtained between two dimensional and three dimensional simulation. Reverse flow which occurs in the mixing chamber made the static pressure in the area has increased dramatically. Then the variation performed on Exit Nozzle Position (NXP) to determine the changes of the flow of the NCG and the vacuum level of the ejector.Keywords: Ejector, NCG, CFD, Compressible flow.